A study on the correlation between the abdominal circumference of neonates and gestational age (Journal of Pharmaceutical Negative Results, 2023)
Normal fetal growth is characterized by cellular hyperplasia followed by hyperplasia and hypertrophy and lastly by hypertrophy alone. Most fetuses follow a very similar growth curve during the first half of pregnancy and any slowing of growth usually occurs in the second half. Fetal growth does not occur at a uniform rate but rather changes over gestation. The rate of growth in the normal fetus various with gestational age, with an increasing exponential curve, in the 1s trimester. A linear curve in the 2nd trimester and most of the trimester and a decreasing exponential curve after 37weeks of gestation.1